2016
DOI: 10.1371/journal.pone.0151041
|View full text |Cite
|
Sign up to set email alerts
|

A New Nanobody-Based Biosensor to Study Endogenous PARP1 In Vitro and in Live Human Cells

Abstract: Poly(ADP-ribose) polymerase 1 (PARP1) is a key player in DNA repair, genomic stability and cell survival and it emerges as a highly relevant target for cancer therapies. To deepen our understanding of PARP biology and mechanisms of action of PARP1-targeting anti-cancer compounds, we generated a novel PARP1-affinity reagent, active both in vitro and in live cells. This PARP1-biosensor is based on a PARP1-specific single-domain antibody fragment (~ 15 kDa), termed nanobody, which recognizes the N-terminus of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 65 publications
2
29
0
Order By: Relevance
“…Since their first description in 2006 (26), chromobodies directed against numerous antigens, including cyokeratin-8, laminA/C, PCNA, actin, b 2 -AR, b-catenin, gH2AX, and PARP-1, have been developed and applied in various cellular models as well as in whole organisms (26)(27)(28)(29)(30)(31)(32).…”
Section: Vimentin-specific Chromobodies Visualize Emt In Living Cellsmentioning
confidence: 99%
“…Since their first description in 2006 (26), chromobodies directed against numerous antigens, including cyokeratin-8, laminA/C, PCNA, actin, b 2 -AR, b-catenin, gH2AX, and PARP-1, have been developed and applied in various cellular models as well as in whole organisms (26)(27)(28)(29)(30)(31)(32).…”
Section: Vimentin-specific Chromobodies Visualize Emt In Living Cellsmentioning
confidence: 99%
“…Being at the starting point of the DNA repair process, PARP1 is also an attractive drug target for the development of anticancer agents. To address the pressing need to better understand PARP1 dynamics in living cells, a fluorescent reporter for tracking endogenous PARP1, named PARP1 chromobody, was generated by fusing an FP to a well-characterized PARP1 nanobody [84]. Consistent with results from other studies, PARP1 chromobody was shown to be capable of tracking the dynamic localization patterns of endogenous PARP1 under various conditions, suggesting its potential as a useful tool for understanding the multiple functions of PARP1 in its native cellular environment.…”
Section: Nanobodies As a Unique Sensing Elementmentioning
confidence: 55%
“…At the cellular level, intrabodies have been used to interfere with protein-protein interactions in oncogenic pathways [272] and to influence processes involved in proliferation, the cell cycle and apoptosis. DNA repair and genomic stability were studied by a nanobody fused to a fluorescent protein that allowed tracking of poly (ADP-ribose) polymerase 1 (PARP1), a target for cancer therapy to inhibit DNA repair for sensitizing tumour cells to radio-or chemotherapy [273]. Several proof-of-concept studies have demonstrated downregulation of human epidermal growth factor receptor-2 (HER2) or inhibition of cell proliferation by intrabodies targeting HER2 [272,274].…”
Section: Applications In Oncology: Targeting At the Cellular Levelmentioning
confidence: 99%